CONTEMPORARY TRENDS IN THE TURISM MARKET - Mateta Gigova, Dusica (Journal of process management and new technologies, 2016)
By the term market, in the widest since of the word, means a set of everyday relations of demand and supply to various types of goods, in which the exchange is carried out through the intermediation of money. As a mixture of the interaction between supply and demand, the market is actually a mixture of the overall supply and overall demand for goods and services, production resources and loans. These relations act constantly, in a certain time and place. It is a mixture of legal interaction between supply and demand. The market is a summation of all facilities, zones and offices that provide organized and constant contact between buyers and sellers, or encounter of the supply and demand, which leads to the implementation of goods. The basic idea of the market can be defined as material and immaterial centralization and concentration of supply and demand in one or more economic goods within a specified period of time. Accordingly, in the widest sense, the market is part of the socio-economic system and its functions are - by means of it to realize reproduction of material production, and the occalist manufacturing relations. The market is a particular place where you meet the seller and the buyer and where are concluded bills of sale. It can be: shop, marketplace, daily or weekly market, an annual trade fair (fair), contemporary fair of samples, stock market , purchase or sale of department of industrial or wholesale trading company. The term "market" can mean territory (zone).